ILLOCUTIONARY ACT IN KARATE KID’S MOVIE - Eva Inriani Rajagukguk; Bachtiar Bachtiar (State University of Medan, 2014)
ABSTRACT The study deals with the types of illocutionary act usedin Karate Kid’s Movie. The objectives of the study were to discover the dominant illocutionary act and to implicate for the use dominant illocutionary act in movie. The data were the transcript of Dre Parker’s utterances which were downloaded from internet.This research was conducted by using descriptive qualitative design. The findings showed that there were 220 utterances which contained 4 types of illocutionary act. Dre Parker tended to use the representative (54, 55%), directive (34, 50%), expressive (8, 18%),and commissive (2, 72%). The most dominant type of illocutionary act was representativebecause he mainly used the statement of arguing, asserting, informing and describing. Keyword : illocutionary act, types of illocutionary act, movie